The Total Social Costs of Constructing and Operating a High-Speed Rail Line Using a Case Study of the Riyadh-Dammam Corridor, Saudi Arabia - Almujibah, Hamad; Preston, John (Frontiers in Built Environment, 2019)
Constructing High-Speed Rail technology between the Saudi Arabian cities starts raising many challenging issues of a different nature ranging from technical to operational, which require huge investments in infrastructure, operations, and maintenance. However, this paper develops a new methodology to calculate the total social costs of building a new HSR worldwide and applies this using the case study of the Riyadh-Dammam corridor in Saudi Arabia. This is done through a Spreadsheet Cost Model mainly based on Microsoft Excel that includes operator cost, user cost, and external cost. In order to determine the total social costs of a Riyadh-Dammam HSR line, the annual travel demand is forecasted of 13,205,212 passengers in the first year of operation. In this case, the gravity demand model is used to forecast the demand, as a function of independent variables for the cities alongside with the proposed line such as the population, GDP per capita, the generalized journey time, unemployment rate, years since opening the corridor, and the dummy variable. As a result, the total social costs of constructing and operating the proposed HSR line is €1,090,106,913 per year resulting from the sum of the following categories. First, the total operator cost (OC) is €859,797,307 per year, which is mainly based on the total infrastructure and rolling stock costs of €750,852,759 per year and €108,944,548 per year, respectively. Second, the total user cost is €216,769,247 per year resulting from the sum of total annual passenger access/egress time, waiting time, and in-vehicle time. Finally, the total external environmental cost is €13,540,359 per year resulting from the sum of average costs of noise and air pollution, climate change, and accident.